Effect of Milling Time on Physical and Mechanical Properties of Ceramics Derived from the CaO-MgO-Al2O3-SiO2 System - Ismail, Hamisah; Mohamad, Hasmaliza; Hussin, Rosniza (Emerging Advances in Integrated Technology, 2022)
This study produced ceramics powder derived from the CaO-MgO-Al2O3-SiO2 system using mechanical wet milling and cold pressing method. The milling time was changed between 30 min to 2 h and sintered at 950 ?C for 1 h. The pellet was performed via cold pressing in ambient temperature and pressure of 5 tonnes. The effect of milling time on the linear shrinkage, density, porosity and compressive strength of the derived from CaO-MgO-Al2O3-SiO2 system were investigated. X-ray diffraction results demonstrated that a multi-phase of quartz and akermanite-gehlenite was obtained after sintering at 950 °C for 1 h. The results show that the increasing milling time had significantly affected the ceramics’ particle size, specific surface area, phase, linear shrinkage, density, porosity, compressive strength and Young’s modulus. When the milling time was raised, the density and compressive strength decreased. However, the increase in milling time increased the linear shrinkage and porosity. It was observed that the compressive strength of the pellets reached their maximum value (16.6 MPa) at a milling time of 1h and then decreased with increasing milling time.